2016
DOI: 10.1016/j.aop.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Eisenhart lifts and symmetries of time-dependent systems

Abstract: Certain dissipative systems, such as Caldirola and Kannai's damped simple harmonic oscillator, may be modelled by time-dependent Lagrangian and hence time dependent Hamiltonian systems with n degrees of freedom. In this paper we treat these systems, their projective and conformal symmetries as well as their quantisation from the point of view of the Eisenhart lift to a Bargmann spacetime in n + 2 dimensions, equipped with its covariantly constant null Killing vector field. Reparametrization of the time variabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 68 publications
(148 reference statements)
1
56
0
Order By: Relevance
“…pp-wave space-times play a role for the Eisenhart-Duval lift [12][13][14]16] of 2-dimensional classical dynamics. Analysing the meaning of the charges in this context, we have shown that after expressing them in terms of transversal coordinates, the term with m reduces to a constant.…”
Section: Discussionmentioning
confidence: 99%
“…pp-wave space-times play a role for the Eisenhart-Duval lift [12][13][14]16] of 2-dimensional classical dynamics. Analysing the meaning of the charges in this context, we have shown that after expressing them in terms of transversal coordinates, the term with m reduces to a constant.…”
Section: Discussionmentioning
confidence: 99%
“…(19) also implies that the spacetime (12) admits a geodesic null congruence with vanishing expansion, shear and vorticity and thus belongs to the Kundt class. The distinguished vector field ξ µ can be used to construct the trace-free energy-momentum tensor 4 T 4 The factor d 2π , d being the dimension of the x-subspace, is chosen for further convenience.…”
Section: The Eisenhart Liftmentioning
confidence: 99%
“…where ǫ = 0 for the null geodesics and ǫ = −1 for the time-like geodesics. Given the general solution in (4), the dynamics of the extra variable s is unambiguously fixed by the first order ordinary differential equation (34). Thus the original dynamical system (1) is recovered if one implements the null reduction along s.…”
Section: Conformal Mode As a Scale Factor In The Eisenhart Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial motivation for this research was to have a deeper understanding of the torsion condition. In nonrelativistic holography the bulk metrics are a pp-wave generalization of AdS spaces [38], clearly related to so called Eisenhart-Duval lift metrics [23,26,[39][40][41][42][43]. However, Eisenhart-Duval lift metrics have always been studied in the context of zero torsion.…”
mentioning
confidence: 99%